1, 25‐dihydroxyvitamin D3 regulates the development of chronic colitis by modulating both T helper (Th)1 and Th17 activation. Issue 6 (23rd April 2015) - Zhang, Hong; Wu, Hui; Liu, Lei; Li, Hui; Shih, David Q.; Zhang, Xiaolan
<x xml:space="preserve">Abstract</x> T helper (Th)1 and Th17 cells play a critical role in inflammatory bowel disease (IBD). 1, 25‐dihydroxyvitamin D3 (1, 25(OH)2D3) has emerged as a direct regulator of immune system function. Mice were grouped as follows: Control group (received PBS, n = 10), DSS group (received 2% DSS and PBS, n = 10), and DSS+VD group (received 2% DSS and 1, 25(OH)2D3, n = 10). The disease activity index (DAI), colon length, and damage store of the mice were observed; the spleen length, weight, spleen index, and mononuclear cells of spleen were measured; mononuclear cells from mesenteric lymph nodes (MLN) were measured, and the levels of Th 1 and Th17 cytokines in the colon mucosa and spleen were measured. Mice in the DSS group developed severe diarrhea, rectal bleeding, and marked BW loss. Histological examination revealed extensive ulceration and inflammatory cell infiltration in the colon, and the structure of the spleen was disordered, infiltrated with inflammatory cytokines in red pulp. In the DSS group, mononuclear cell numbers from MLN and spleen were increased, and enhanced proteins and mRNA levels of Th 1 and Th17 cytokines were detected. In the DSS+VD group, 1, 25(OH)2D3 ameliorated the inflammation of the colon and spleen. In addition, 1, 25(OH)2D3 down‐regulated the levels of Th 1 and Th17 cytokines. 1, 25(OH)2D3 represents a novel therapeutic drug for UC, which may correlate to inhibit the activation of Th1 and Th17 cells.